Properties of titanium carbide reinforced aluminium silicon alloy matrix - M. Sayuti, (2012)
Metal matrix composites are engineered materials which are a combination of two or more materials, one of which is a metal, whose tailored properties can be attained by systematic combination of different constituents. From a variety of methods available for producing these advanced materials, the conventional casting process is considered as the easiest processing technique. Preparation of these composite materials by foundry technology has the unique benefit of near-net shape fabrication in a simple and cost effective manner. Besides this,casting processes lend themselves to manufacture large number of complex shaped components of composites at a faster rate required by the automotive,aerospace, sports and other consumer oriented industries. Several methods have been developed to control the microstructure of composites during solidification including mechanical vibration, electromagnetic vibration,electromagnetic stirring and semi-solid processing. It is established that mechanical mould vibration can significantly enhance the structure and properties of composites. In this study, titanium carbide particulate reinforced aluminiums 11,8 wt% silicon alloy matrix composites were fabricated by carbon dioxide sand moulding process by varying the particulate addition by weight fraction on percentage basis using mechanical vibration mould. The influence of a wide range of vibration amplitudes and frequencies on the solidification kinetics, microstructure formation and mechanical properties of Titanium carbide reinforced aluminiums 11,8 wt% silicon alloy were examined. Results show strong influence of mould vibration during solidification on the fabricated composites. The mechanical properties such as tensile strength, impact strength, surface hardness and physical properties such as density, thermal conductivity were significantly increased as a result of mould vibration. The maximum tensile strength is 141.125 MPa with vibration and 135.832 MPa without vibration. The maximum impact energy is 15.073 kJ with vibration and 14.514 kJ without vibration and hardness value based Rockwell superficial 15N-S scale is 85.88 for 2% without vibration and 86.08 with vibration. In addition, the change in microstructure and mechanical properties were successfully represented by the changes in solidification characteristics. Various vibration frequencies have reduced the lamellar spacing that changes the microstructure of the composites which as a result became more fibrous. The corresponding changes in mechanical properties indicate that ductility is more influenced by vibration than without vibration. The increase in ductility was believed to be due to the structural refinement.